Perlindungan Hukum terhadap Pemilik Sertifikat Hak Atas Tanah yang Dikuasai oleh Pihak Ketiga Tanpa Hak - Simauli Margaretta Panjaitan; Besty Habeahan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
A land certificate serves as the strongest form of ownership evidence; however, conflicts over physical possession frequently occur, leading to legal uncertainty. This study examines the legal protection afforded to legitimate owners of land certificates whose land is unlawfully possessed by third parties. The 1945 Constitution of the Republic of Indonesia guarantees and protects the rights of Indonesian citizens, including their rights to acquire, own, and enjoy land ownership. The research employs a normative juridical method by analyzing relevant laws and regulations, such as the Basic Agrarian Law Number 5 of 1960 and Government Regulation Number 24 of 1997 concerning Land Registration. The data sources used in this study consist of both primary and secondary materials. The main issues addressed include the form of legal protection available to land certificate holders whose land is unlawfully controlled by third parties, and the legal remedies that may be pursued by the rightful owners to reclaim their rights. The findings indicate that legal protection for land certificate holders can be implemented through both preventive and repressive measures. Preventive protection is achieved through a land registration system that ensures legal certainty, while repressive protection is pursued through dispute resolution mechanisms in court. These mechanisms are expected to safeguard the rights of landowners and ensure the realization of legal certainty in a fair and equitable manner.